Understanding Constraints and Facilitators to Salmon Angling Participation: Insights From Structural Equation Modeling - Stensland, Stian; Aas, Øystein; Mehmetoglu, Mehmet (Human Dimensions of Wildlife, 2017)
Atlantic salmon sport fisheries have declined remarkably in many countries and participation seems to correlate with salmon abundance. We investigated angling participation in the Atlantic salmon sport fishery in Norwegian rivers by incorporating facilitators for participation in a constraint–negotiation model. We conducted an Internet survey of Norwegian anglers yielding 3,635 responses (40% response rate). The structural model confirmed our hypotheses and supported the conceptual constraints-effects-mitigation model of leisure constraint negotiation. Of the constraints and facilitators investigated, the structural constraints and facilitators subcategory “quality of fishing” exerted the largest influence on angling participation. The influence of constraints and facilitators was mitigated by use of corresponding negotiation strategies where “skills, knowledge, and money,” and different substitution strategies were important. To increase participation, we suggest increasing salmon abundance, offering longer fishing stretches per angler, and providing better information about where to book salmon angling. acceptedVersion This is an Accepted Manuscript of an article published by Taylor & Francis in Human Dimensions of Wildlife on , available online: http://www.tandfonline.com/doi/full/10.1080/10871209.2016.1199073 . Locked until 29 December 2017 due to copyright restrictions.